Does Digital Marketing Enhance Rural Agricultural Transformation in Nigeria? An Empirical Investigation - Ogbeide-Osaretin , Evelyn Nwamaka; Ebhote, Oseremen (Asian Journal of Agriculture and Rural Development, 2020)
The rural transformation has been noted as an important national policy goal. This requires among other things the use of recent technology to enhance agricultural production. This study examined the role of digital marketing in rural transformation. The objective of the study was to determine the impact of digital marketing using ICT devices on Nigeria’s rural transformation. Nigeria’s time-series data on agricultural value-added was used as a measure of rural transformation on some measures of digital marketing (the percentage of internet users and the proportion of mobile users). Rainfall and some control variables were also included over the time from 1995 to 2018. Ordinary least square estimation method was employed in a linear model as no cointegration was found among the variables, proved by the bound testing result. The outcome showed that digital marketing is positively and substantially related to rural transformation. We hence, advocate that digital marketing be strongly encouraged by providing the needed infrastructure facilities as well as increasing the availability of education in the rural areas among others.